Climate change politics and policies in America : historical and modern documents in context - Mast, Jerald C. (ABC-CLIO, An Imprint of ABC-CLIO, LLC, 2019)
This extensive collection of primary documents examines the history of climate science; various policy prescriptions for addressing the effects of climate change; political fault lines with respect to international efforts to address global warming; claims regarding the influence of industry groups and environmental "radicals" on climate policy and science; and the impact of climate change on other policy areas such as public health, energy, economic development, and wilderness conservation. The set includes excerpts from important scientific papers and government reports, political speeches from presidents and other influential lawmakers, perspectives from environmental activists and conservative think-tanks, editorial essays from leading media figures, provisions of major laws, and more. Together, these documents provide a broad range of perspectives, from scientific fields as well as from political and ideological standpoints that have emerged in response to the debate surrounding climate change. They offer readers a greater understanding of the arguments not only of lawmakers, activists, and scientists leading efforts to fight, mitigate, and adapt to climate change but also of those skeptical of climate change.